The impact of TRAIL on proliferation of secretory prostate cancer PC-3 cell and LMO2 gene expression - Che, Z; Li, H-W; Wang, P; Jiang, B; Li, B; Zhao, K; Wang, S-P; Gao, H; Zhang, M-Q (European review for medical and pharmacological sciences, 2018)
To determine the expressions of TRAIL protein and LMO2 gene in prostate cancer tissues with different differentiation degree and identify the influence of TRAIL on prostate cancer PC-3 cell proliferation. Surgical specimens from a total of 30 prostate cancer patients with radical prostatectomy were collected. The subjects were divided into three groups according to the different degrees of differentiation. TRAIL positive rate was detected by immunohistochemistry (IHC). LMO2 expression was assessed by Real-time PCR and Western-blot. PC-3 cell proliferation was determined by CCK-8 assay. The positive rate of TRAIL protein was significantly higher in moderately differentiated group (80%) and well differentiated group (100%) compared with that in poorly differentiated group (54.55%), respectively (χ2 = 27.33, p < 0.05; χ2 = 40.12, p < 0.01). Streptavidin-peroxidase (SP) assay showed that TRAIL protein expression in well-differentiated group was significantly higher than that in moderately differentiated group and poorly differentiated group. qRT-PCR result demonstrated that LMO2 mRNA levels in moderately and well-differentiated group were significantly increased compared to that in poorly differentiated group (p < 0.001). Also, the proliferation rate of PC-3 cells in well-differentiated group was significantly higher than that in well-differentiated and moderately differentiated groups (p < 0.05). Our data indicated that the positive rate of TRAIL protein increased in a prostate cancer differentiation dependent manner.